PHYSIOTERAPY PROGRAM IN NON-OPERATIVE GRADE 2 ANTERIOR CRUCIATE LIGAMENT INJURY: A CASE STUDY - Prasetyo, Agus; Rahman, Farid; Prayitno, P (Universitas Muhammadiyah Surakarta, 2021)
Introduction: An ACL injury is a damage to the anterior cruciate ligament (ACL), which is the strong tissue that helps connect the femur and tibia. ACL injuries most often occur during sports activities such as football, basketball, badminton that have a lot of motion during sudden stops, changes of direction, jumps, and landings. The incidence of ACL injuries is estimated to range from 30 to 78 per 100,000 people annually. Generally, ACL injuries are performed by ACL reconstruction procedures to restore joint motion function in the knee. However, some people with ACL injuries choose not to undergo ACL reconstruction due to various factors that underlie their reasons. Some of them managed to return to some level of function with non-operative management. Therefore, the role of physiotherapy in non-operative ACL management is to prevent more severe tissue damage, restore movement function and maximize strength by modifying the patient's daily movements or activities to become more optimal. Case Presentation: A 27 years male. He works as a private employee, residing in Solo, Central Java. examinations that have been carried out on the patient found muscle stiffness and tenderness and pain in motion and positive findings were also found during a specific examination using the anterior drawer test and the Lachman test. Management and Outcome: Physiotherapy modalities with infrared, Kinesio taping myofascial release, and combined with muscle strengthening exercises can reduce pain and muscle spasms in ACL patients with non-operative procedures. Furthermore, to determine the patient's progress, measurement results were used in the form of a Numeric Rating Scale ( NRS ) to measure pain, Manual Muscle Testing ( MMT ) to measure muscle strength and Knee injury, and Osteoarthritis Outcome Score ( KOOS ) to measure knee function. Discussion: Several studies have revealed that the use of infrared modalities, Kinesio taping, myofascial release by adding muscle strengthening exercises have a positive effect in reducing pain and stiffness in muscles in cases of ACL injuries. The author tries to prove it by applying several modalities that have been studied previously Conclusion: The physiotherapy program which was carried out in 3 weeks with the physiotherapy modalities used such as Infrared, Myofacial Release, Kinesio Taping, and Strengthening Exercises was able to reduce pain and restore body functions to carry out daily activities. however, no significant increase in muscle strength was found. It can be concluded that this exercise is effective for the short term and helps restore the patient's functional activity.